Coopetition in the SoC industry: The case of Qualcomm Incorporated - Yona Kwon; Dahee Kang; Sinji Kim; Seungho Choi (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
This study uses the lens of competitive dynamics to examine the coopetition process, which combines both cooperation and competition, employed by Qualcomm within the SoC (System on a Chip) design market related to smart devices. Qualcomm succeeded in developing the first SoC, which integrated GPS (Global Positioning System) and other software, and during the process of developing mobile chips has simultaneously cooperated and competed with competitors. In particular, Samsung, which began as a customer of the firm, has since become its competitor. By conducting descriptive case analysis, this study shows a coopetition process in the SoC industry and supplemented a coopetition study with the actual exemplary coopetition case.
Keywords: 650; Competitive Dynamics; Coopetition; Qualcomm; System on Chip Industry